In innovative approach to the teaching of Homers Odyssey at A class of Greek Gymnasium based on the educational material Seafaring and civilizations of the Odyssey 1 and Odysseus raft 2 (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
This research attempts to investigate qualitatively and within the context of teaching of students of A class of Gymnasium in the Odyssey and teachers who teach the Odyssey, the relationship between cognitive performance with teaching materials "Seafaring and civilizations of the Odyssey" and "Odysseus raft". The survey involved both students and teachers of the A class of Gymnasium of a public School. The students attended a course which was constructed diversified as to course material teaching. The selected research tools included a questionnaire for teachers, a questionnaire (assessment tests) for students, students worksheets and observation of students and the research was carried out by the researcher. The analysis of the obtained data shows that the implementation of teaching with specific teaching materials had a positive effect on performance and student learning.